English Needs Analysis for Nursing Students: A Workplace Survey for Designing English for Nursing Purposes Materials - Lia Febriani; Engkartini Engkartini (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Need analysis is an important stage before designing the material English for Specific Purposes. The study aims to (1) identify the role of English in a healthcare setting (2) identify the need of English for nursing students in their workplace (3) design the appropriate syllabus for nursing students at Al-Irsyad University of Cilacap. The respondents were nurses studying for bachelor’s at UNAIC and working in some health settings in Cilacap. A learner-centered learning approach was applied in this study. The result of the study showed they hardly ever practiced English in their workplace with a mean of reading (1,8), listening (1,6), writing (1,5), and speaking (1,3). The need of English for nursing in their workplace was neither rare in using. They had difficulties in learning four English skills with a mean for speaking (2,4), listening (2,3), reading (2,2), and writing (2,1). Nevertheless, they thought that English was important for them to obtain information, get a scholarship, and fulfill their personal needs. Some material topics were mentioned to learn during the nursing study such as checking identity bracelets and some therapeutic communication topics. Based on the result mentioned, the syllabus is then designed with the four skills in English and put them all in their learning.